Est Deus in nobis or the Will to Enjoy - Šumič Riha, Jelica (Filozofski vestnik, 2017)
In “Kant with Sade”, Lacan stages two incompatible couples, incompatible precisely to the extent that they bring together reason and jouissance: Kant and Sade on the one hand and Sade with Epictetus on the other. If Sade is coupled with Kant in order to reveal a hidden driving force behind Kant’s moral law, Epictetus’ joining Sade is revelatory of Sade’s deficiency as a desiring subject. Following Lacan’s indications concerning the radical change of the status of the subject resulting from the establishment of an unheard of relationship between desire and will at the end of analysis, this essay examines two modalities of the subject’s confrontation with the Other’s will to enjoy: Sade’s and Stoics’. Insisting on a few crucial points of convergence and divergence of these two modalities of the subject’s coming to terms with the will to jouissance, the author aims to explore the conditions of possibility of an ethics without the Other, an ethics of the drive, to be precise, that allows for a non-perverse transgression of the pleasure principle.